2003
DOI: 10.1042/bj20021646
|View full text |Cite
|
Sign up to set email alerts
|

Physical interaction of tumour suppressor p53/p73 with CCAAT-binding transcription factor 2 (CTF2) and differential regulation of human high-mobility group 1 (HMG1) gene expression

Abstract: The CCAAT-binding transcription factor (CTF)/nuclear factor I (NF-I) group of cellular DNA-binding proteins recognizes the sequence GCCAAT and is implicated in eukaryotic transcription, as well as DNA replication. Molecular analysis of human CTF/NF-I cDNA clones revealed multiple mRNA species that contain alternative coding regions, apparently as a result of differential splicing. Expression and functional analysis established that individual gene products can bind to GCCAAT recognition sites and serve as both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 49 publications
1
39
0
1
Order By: Relevance
“…The plasmid construction of pGEX-p53 expressing GST-p53, TH-HA-p53 expressing N-terminal tagged HA-p53, pcDNA3-HA-p53, ThioHis-p53 and its deletion mutants (N376, N362, N322, N223, 60C, N160, 224C, 161/223; see Figure 2a) has been described previously Uramoto et al, 2002Uramoto et al, , 2003. The ThioHis-p53 deletion mutant D138-159 was constructed from the ThioHis-p53 full-length plasmid by deletion of the MlsI fragment.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…The plasmid construction of pGEX-p53 expressing GST-p53, TH-HA-p53 expressing N-terminal tagged HA-p53, pcDNA3-HA-p53, ThioHis-p53 and its deletion mutants (N376, N362, N322, N223, 60C, N160, 224C, 161/223; see Figure 2a) has been described previously Uramoto et al, 2002Uramoto et al, , 2003. The ThioHis-p53 deletion mutant D138-159 was constructed from the ThioHis-p53 full-length plasmid by deletion of the MlsI fragment.…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…Plasmid construction of pGEX-p53, pGEX-p73 and pGEX-ZNF143 that express GST-p53, GST-p73 and GST-ZNF143 proteins in bacteria, respectively, and pcDNA3-HA-p53 that expresses HA-p53 protein in mammalian cells were described previously (Imamura et al, 2001;Uramoto et al, 2002Uramoto et al, , 2003. pcDNA3-HA-p73 expression plasmid in mammalian cells was kindly provided by Dr G Melino (University of Rome, Rome, Italy) (De Laurenzi et al, 1998).…”
Section: Plasmid Constructionmentioning
confidence: 99%
“…5). It has been shown that the p73 protein is regulated by diverse factors, including MDM2, MDMX, p300/ CBP, Amphiphysin IIb-1, ASPP (apoptosis-stimulated proteins of p53) 1 and 2, c-Abl (cellular Abelson oncogene), c-Myc, CTF2 (CCAATbinding transcription factor 2), Cyclin G, HCV (hepatitis C virus protein), MM1, PMS2 (mismatch-repair protein s2), WT1 (Wilms tumor protein), and YAP (Yes-associated protein) (15,16,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43). Among these regulators, MDM2 is a well known repressor of p73 and p53, but its inhibitory effect on p73 does not involve degradation.…”
Section: P19mentioning
confidence: 99%